PQRST in Teaching Reading Comprehension for the First Semester students of Nursing Study Program STIK SITI KHADIJAH Palembang - Nyayu Yayu Suryani; Surya Darma; Arif Pamuji (ELT-Lectura, 2020)
Abstract: The objectives of this study were to find out : (1) the significant improvement on the first semester students’ reading comprehension before and after being taught using PQRST technique at STIK Siti Khadijah Palembang, South Sumatera, Indonesia; and (2) the significant difference on students’ reading comprehension between the students who were taught by using PQRST technique and those who were not. The population of this research was all the first semester students of STIK Siti Khadijah Palembang which consist of 32 students in academic year 2019/2020. The sample of this research was taken by using total sampling. Thus, the total number of the sample was 32 students. The sample was the first semester students at Nursing Study Program (experimental group) which consist of 32 students and the third semester students at D.III Nursing Study Program (control group) which consist of 32 students. The test was given twice to both experimental and control group. True experimental design was used to analyzed the data. To verify the hypotheses, the data used post-test design to analyzed by using paired sample t-test and independent sample t-test was 0.005 which was lower than 0.05.The result of this research showed that Reading Comprehension by using PQRST technique gave significant improvement on the students’ reading comprehension and gave significant difference between students’ who were taught by PQRST technique and those who were not. Keywords : Reading Comprehension, PQRST